2011
DOI: 10.1063/1.3624705
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneity improvement of field emission beam from metallic nano-tip arrays by noble-gas conditioning

Abstract: The authors explored control of field-emission electron beam homogeneity emitted from metallic nano-tips fabricated by molding. Improved beam homogeneity and increased maximum bunch charge were observed after DC operation of cathodes in low-pressure argon gas environment. They also observed average current per tip of 4.5 lA from a 1 Â 10 4 emitter array device after conditioning in neon gas. Evolution of Fowler-Nordheim parameters as a result of noble-gas conditioning was discussed. V

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…This fact is attributed to the increase of the number of active emitters together with the blunting of the sharpest emitters by bombardment of neon ions. 15 This interpretation is also compatible with the improvement of the beam uniformity. The granularity of the beam image of Fig.…”
Section: Fea Fabrication and Experimentssupporting
confidence: 67%
See 1 more Smart Citation
“…This fact is attributed to the increase of the number of active emitters together with the blunting of the sharpest emitters by bombardment of neon ions. 15 This interpretation is also compatible with the improvement of the beam uniformity. The granularity of the beam image of Fig.…”
Section: Fea Fabrication and Experimentssupporting
confidence: 67%
“…These values and the predicted field emission pulse amplitude (with the average tip current of $1 lA) are within the reported parameter range of the all metal single-gate FEAs considered here (after the neon gas conditioning) as shown in previous experiments. 15 The potential V ge,edge at r edge (¼2 mm) with duration of $40 ps propagates to the center of the FEA in $20 ps as shown in the upper panel of Fig. 9(a).…”
Section: Simulation At Short Switching Time Scalementioning
confidence: 99%
“…12 With the 10 4 tip array, this has been achieved with the help of a noble gas conditioning process which can also improve the beam uniformity. The proposed mechanism assumes impact ionization of noble gas molecules close to the current emitting tips and subsequent ion bombardment of these tips.…”
Section: Discussionmentioning
confidence: 99%
“…Research on field emitter arrays (FEAs) has been actively pursued [1][2][3][4][5][6][7][8][9][10][11][12][13] with the aim of realizing high current and high current density cathodes, e.g., for compact microwave vacuum electronic amplifiers, such as traveling wave tubes (TWTs) [14][15][16][17] and compact free electron lasers. 7,18 FEAs are expected to help simplify the gun design and extend the operation range of such TWTs.…”
Section: Introductionmentioning
confidence: 99%
“…Another promising method is the bombardment of ions generated by glow-discharge 28 or by electron impact ionization using the field emission current. [29][30][31][32] In particular, an improvement of the beam uniformity by in-situ noble gas conditioning for single-gate molybdenum FEAs was demonstrated recently. 32 However, no study has been reported for the beam uniformity control of double-gate FEAs.…”
mentioning
confidence: 99%